A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF SMP N 2 KUBU BABUSSALAM IN WRITING PROCEDURE TEXTS - Ramadina Setia Bahar; Supriusman Supriusman; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aimed to find out the ability of the students in writing procedure texts made by the third year students of SMP Negeri 2 Kubu Babussalam. This is quantitative descriptive research. The populations of this research were the third year students of SMP Negeri 2 Kubu Babussalam. The sample of this research was 25 students of 9.1 classes who have been selected using cluster-sampling technique. The data were collected by using writing test. The data were analyzed by applying the rules of Brown (2007) through three raters. The findings of this study revealed that the students ability of the third year students of SMPN 2 Kubu Babussalam in writing procedure texts in the 2020/2021 academic year is in good level. The students’ mean score in writing a procedure text is 69.1. To be more specific, 5 students are categorized as excellent, 17 students are categorized as good, 3 students are categorized as mediocre, and there are no students categorized as poor. Based on the findings, there are have recommendations given to the students to improve their ability in writing; to pay attention to vocabulary and grammar, so the students should doing more writing activity especially in writing procedure text and learn more also understand about grammar used.Key Words: Ability, Writing, Procedure Text